Pengaruh Beban Kerja, Lingkungan Kerja, Kompensasi dan Pengembangan Karir Organisasi terhadap Kepuasan Kerja Karyawan di PT. Beton Prima Indonesia - Wahyu Apiyanto, Muhammad; Setyariningsih, Eny; Kasnowo, Kasnowo (Akmenika: Jurnal Akuntansi dan Manajemen, 2024)
This study aims to determine the Effect of Workload, Work Environment, Compensation and Organizational Career Development on Employee Job Satisfaction at PT Beton Prima Indonesia, either partially or simultaneously. The samples in this study were 44 employees. The method of determining the sample in this study uses a saturated or census sample. Data collection was carried out by distributing questionnaires. The data analysis technique uses multiple linear regression analysis with the help of the IBM SPSS program. The results showed that workload (X1) partially had no effect on employee job satisfaction (Y) with a t count -0.241 <t table 2.022 with a significance level of 0.811. The work environment (X2) has no partial effect on employee job satisfaction (Y) with a t count of 1.411 < t table of 2.022 with a significance level of 0.166. Compensation (X3) has a partial effect on employee job satisfaction (Y) with a t count of 23,425 > t table of 2.022 with a significance level of 0.001. Career development (X4) has no partial effect on employee job satisfaction (Y) with a t count of 0.053 <t table of 2.022 with a significance level of 0.958. Workload (X1), work environment (X2), compensation (X3) and career development (X4) simultaneously influence employee job satisfaction (Y) with an F count of 197.722 > F table of 2.612 and a significance level of 0.001.